Assessment of longitudinal pavement marking conditions based on deep learning - Bronuela-Ambrocio, Lea B.; Antes, Emilson Ryan D.; De Leon, Mellaine Denise S. (2023)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/9141/8070
Keywords: Traffic engineering; Road markings; Image processing